Molecular and Biosafety Perspectives of Bacterial Self-Healing Concrete: From Sporulation and Biomineralization to Public Health Implications - Cecilia Manrique-Sam; Ronel Rivas-Torres; Alejandro Miranda-Pinto; Johany Cecilia Sanchez Guillen; Sandra Apaza-Tosocahua; Fernando Farfán-Delgado (Materials, 2026)
Bacterial self-healing concrete has emerged as a bio-based strategy to enhance the durability of cementitious materials and reduce the environmental impact associated with premature infrastructure deterioration. Its functional principle relies on microbially induced calcium carbonate precipitation (MICP), through which bacterial metabolism promotes CaCO3 deposition within cracks. However, self-healing efficiency cannot be explained solely by mineral precipitation capacity. Concrete is a restrictive microbial environment characterized by alkalinity, desiccation, osmotic stress, nutrient limitation and physical confinement. Therefore, effective crack sealing requires a coordinated sequence involving bacterial survival, sporulation, germination, metabolic reactivation, biofilm-associated mineral nucleation and localized biomineralization. This integrative narrative review synthesizes mechanistic, material and biosafety evidence on bacterial self-healing concrete, focusing on spore-forming bacteria such as Bacillus subtilis and related taxa, including Paenibacillus. The evidence indicates that stress tolerance, germination signaling, calcium handling, biofilm establishment and stability, and encapsulation-mediated microenvironmental control are key determinants of performance, but remain insufficiently integrated into materials-oriented studies. Large-scale implementation also requires preventive assessment of strain persistence, genetic stability, horizontal gene transfer, environmental microbiome interactions and life-cycle exposure scenarios. Bacterial self-healing concrete should therefore be understood as a living or bioactive material system whose responsible development depends on the integration of microbiology, molecular biology, materials science, civil engineering, environmental risk assessment, occupational health, and public health.